Planar Dual-Band Monopole Antenna with an Extended Ground Plane for WLAN Applications - Ayman S. Al-Zayed; V. A. Shameena (International Journal of Antennas and Propagation)
A compact planar microstrip-fed monopole antenna designed for dual-band operation is proposed for WLAN applications. The antenna is composed of a rectangular strip monopole in addition to an inverted-L parasitic element that is connected to the truncated ground plane of the microstrip feed. Besides exciting an additional band of operation, the parasitic element also improves the bandwidth of the band excited by the strip monopole. Several simulated parametric studies are conducted to investigate the effects of each geometrical parameter on the behavior of the antenna. Experimental and simulation results demonstrate that the proposed antenna covers the 2.4 and 5.8 GHz bands utilized in WLAN. In both bands, the proposed antenna exhibits good impedance match, moderate gain (approximately 2 dBi), and sustainable omnidirectional-like radiation patterns in both principal planes. An equivalent circuit model of the antenna is also developed.